CURRENT STRUCTURAL TRENDS OF DEVELOPMENTAL DEFECTS OF ENAMEL IN URBAN AREA OF IASI - Marinela Păsăreanu; Adriana Bălan; Roxana Mocanu; Dana Cristiana Maxim (Romanian Dental Association for Education, 2013)
The gravity of the enamel developmental defects request systematical and ample studies to obtain a more correct image over the size and the characteristics of the injuries, even though their prevalence is relatively decreased. The authors' goal was to study the gravity of the enamel developmental defects at a school population from Iaşi using the usual gravity indexes and the enamel defects score (EDS) for every examined subject. The recordings were done using the modified DDE index chart codes, which presents subtypes and also the extension of the examined defect. The obtained EDS score has a mean that varies from 0.06 at 7 years of age to 0.3 at 11 years of age. For primary teeth the gravity index has the limits between 10% and 20%, respectively 12 cases, and for permanent teeth it's obvious a more dispersed distribution of children with enamel defects, almost each class having been represented. The prevalence of the enamel developmental defects is far from a public health problem, but the gravity indexes with values more than 40% request a new orientation concerning the prevention, the interception and the therapy.